Vol 2 - Tatum, J.B
Contents: Electromagnetic Induction; Dimensions; Properties of Magnetic Materials; Alternating Current; Laplace Transforms; Maxwell’s Equations; CGS Electricity and Magnetism; Magnetic Dipole Moment; Electrochemistry
Keywords: Physics -- Electricity -- Magnetism; Vật lý -- Điện -- Từ